1992
DOI: 10.1111/j.1476-5381.1992.tb14524.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of a high affinity dipeptide NK1 receptor antagonist, FK888

Abstract: 3 FK888 inhibited the contraction of guinea-pig isolated ileum induced by SP in the presence of atropine and indomethacin (a NKI receptor bioassay) with a pA2 value of 9.29 (8.60-9.98).4 FK888 inhibited contractions of rat vas deferens by NKA (a NK2 receptor bioassay) and of rat portal vein by NKB (a NK3 receptor bioassay) at concentrations at least 10,000 times greater than that required to inhibit contractions of guinea-pig ileum. 5 FK888 also inhibited SP-induced airway oedema in guinea-pig after both intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(51 citation statements)
references
References 18 publications
2
48
1
Order By: Relevance
“…In the present LTD 4 studies, L-NAME partially suppressed the induced plasma leakage in central airways, and this inhibitory effect disappeared in the presence of the NK 1 receptor selective antagonist FK888 [17]. We have previously clarified the contribution of tachykinins to LTD 4 -induced plasma leakage in guinea-pig airways, in which FK888 and capsaicin pretreatment, which causes sensory neuropeptide depletion, partially inhibited the induced plasma leakage in central but not in peripheral airways [18].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present LTD 4 studies, L-NAME partially suppressed the induced plasma leakage in central airways, and this inhibitory effect disappeared in the presence of the NK 1 receptor selective antagonist FK888 [17]. We have previously clarified the contribution of tachykinins to LTD 4 -induced plasma leakage in guinea-pig airways, in which FK888 and capsaicin pretreatment, which causes sensory neuropeptide depletion, partially inhibited the induced plasma leakage in central but not in peripheral airways [18].…”
Section: Discussionmentioning
confidence: 97%
“…In the second set of experiments, the effect of L-NAME on LTD 4 -induced airway microvascular leakage was again examined in the presence of NK 1 receptor antagonist, FK888 [17], since a part of LTD 4 -induced airway plasma leakage is caused by NK 1 receptor activation [18]. FK888 (10 mg·kg -1 i.v.)…”
Section: Protocolmentioning
confidence: 99%
“…PIEDIMONTE et al [24] showed that CP-99,994, an antagonist of NK 1 receptors, inhibited plasma extravasation in the rat trachea produced by substance P and by stimulation of sensory nerves with capsaicin. In the present study, pretreatment of rats with capsaicin injection to deplete endogenous tachykinins or intravenous administration of the selective NK 1 receptor antagonist FK888 [16] abolished adenosine-induced plasma extravasation. These findings suggest that adenosine may stimulate the release of tachykinins from sensory nerves, which consequently activate NK 1 receptors on the endothelial cells of the postcapillary venules.…”
Section: Discussionmentioning
confidence: 98%
“…kg -1 ) was studied. The effect of FK888, a selective neurokinin-1 (NK 1 ) receptor antagonist [16], on the adenosine action was also examined. In order to do this, FK888 (10 mg .…”
Section: Methodsmentioning
confidence: 99%
“…(Fujii et al, 1992) (10-1o-10 M), (Snider et al, 1991) (101o°-10-8M), (Desai et al, 1992) Concentration (-IOgM) Figure 5 Effects of tachykinin NK1 and NK2 receptor antagonists on the endothelium-independent contraction induced by substance P (10-7M) in the endothelium-free intrapulmonary artery of the rabbit. dramine (10' M) and [Sar',Ala8]-angiotensin II (10' M) had no effect on the EIC (data not shown).…”
Section: Resultsmentioning
confidence: 99%